Genre analysis and the teaching of academic literacy: a case study of an academic discipline in the social sciences - Vorwerk, Shane Paul (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1998)
Students in tertiary educational institutions in South Africa come from many different backgrounds and have varied educational experiences. Some students, especially those from non-English speaking backgrounds, may encounter linguistic difficulties with various academic tasks. In order for students to be successful at university, they must become academically literate. That is, they must master all the reading, writing, listening and comprehension tasks required by the disciplines in which they are studying. One such task is presented by the academic lecture which is an integral part of any course of study. Linguistically, the academic lecture can be seen as a particular genre with unique characteristics. This study investigated some linguistic characteristics of academic lectures. The discipline of Political Science, as a Social Science, was chosen because there is little research that has been done on language in the Social Sciences. The Political Science sub-disciplines of Political Philosophy, South African Politics, and International Relations were used in this research. First year lectures were recorded from each of these three sub-disciplines. The linguistic characteristics of lectures were analysed using techniques drawn from Systemic Functional linguistic theory. The analysis concentrated on the aspects mode and field as they were realised in the lectures. In addition, higher level generic structure was also analysed. The insights gained from the analysis were validated through interviews with the lecturers who gave the lectures. The aim of this research was to develop a linguistic characterisation of the lecture genre as it occurs in the three sub-disciplines of Political Science. The results of this research suggest that although there is a unified academic lecture genre, there is variation according to sub-discipline. The implications of this variation are discussed with reference to their relevance to teaching academic literacy.
Keywords: Lectures and lecturing; Lecture method in teaching; Language and culture; Discourse analysis; Language and culture -- South Africa; English language -- Discourse analysis; Intercultural communication -- South Africa; English language -- Study and teaching -- South Africa -- Foreign speakers